Sensorimotor Connectivity in Parkinson’s Disease: The Role of Functional Neuroimaging - Tessitore, Alessandro; Giordano, Alfonso; De Micco, Rosa; Russo, Antonio; Tedeschi, Gioacchino (Frontiers in Neurology, 2014)
The diagnosis of Parkinson’s disease (PD) remains still clinical; nevertheless, in the last decades, the rapid evolution of advanced MRI techniques has made it possible to detect structural and, increasingly, functional brain changes in patients with PD. Indeed, functional MRI (fMRI) techniques have offered the opportunity to directly measure the brain’s activity and connectivity in patients with PD both in early and complicated stage of the disease. The aims of the following review are (1) to present an overview of recent fMRI reports investigating the activity and connectivity of sensorimotor areas in patients with PD using both task-related and “resting-state” fMRI analysis (2) to elucidate potential pathophysiological mechanisms underlying dyskinetic motor complications in the advanced stage of PD.